Accumulibacter diversity at the sub-clade level impacts enhanced biological phosphorus removal performance. (1st July 2021) - Kolakovic, Srdana; Freitas, Elisabete B.; Reis, Maria A.M.; Carvalho, Gilda; Oehmen, Adrian
Abstract: Accumulibacter is a well-known group of organisms, typically considered to be polyphosphate accumulating organisms (PAOs), but potentially capable of glycogen accumulating organism (GAO) metabolism under limiting influent phosphate levels. Metabolic features of Accumulibacter are typically linked to its phylogenetic identity at the Type or clade level, though it is unclear the extent to which Accumulibacter diversity can correlate with its capacity to perform P removal. This paper investigates the fine-scale diversity of Accumulibacter and its link with enhanced biological phosphorus removal (EBPR) performance under various operating conditions, to understand the conditions and community structure leading to successful and unsuccessful EBPR operation. For this purpose, the organic carbon feeding rate and total organic carbon concentration were varied during three distinct operational periods, where influent phosphate was never limiting. Accumulibacter was always the dominant microbial group (>80% of all bacteria according to quantitative fluorescence in situ hybridisation - FISH) and low levels of Competibacter and other GAOs were consistently observed (<15% of all bacteria). Steady state was achieved in each of the three periods, with average phosphorus removal levels of 36%, 99% and >99%, respectively. Experimentally determined stoichiometric activity supported the expression of a mixed PAO/GAO metabolism in the first steady state period and the typical PAO metabolism in the other two steady state periods. FISH quantification and amplicon sequencing of the polyphosphate kinase ( ppk1 ) functional gene indicated that Accumulibacter clade IIC was selected in the first steady state period, which shifted to clade IA after decreasing the carbon feeding rate in steady state period 2, and finally shifted back to clade IIC in the third steady state period. Fine-resolution Ppk -based phylogenetic analysis revealed three different clusters within Accumulibacter clade IIC, where clusters IICii and IICiii were linked to poor EBPR performance in period 1, and cluster IICi was linked to good EBPR performance in period 3. This study shows that the deterioration of EBPR processes through GAO activity at non-limiting P concentrations can be linked to organisms that are typically classified as PAOs, not only to known GAOs such as Competibacter . Intra-clade phylogenetic diversity within Accumulibacter showed that some clusters actually behave similarly to GAOs even without influent phosphate limitation. This study highlights the need to closely re-examine traditional interpretations regarding the link between the microbial community composition and identity with the performance and metabolism of EBPR systems. Graphical abstract: Image, graphical abstract